Internal migration and its impact on reducing inter-communal disparities in Chile - Carlos Villalobos Barría (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2012)
Based on the affirmation that internal migration in Chile has become increasingly less important as an equalizing mechanism for regional disparities, this paper aims to look at the causes of such immobility. The estimation procedure allows for obtaining a non-endogenous potential wage differential which controls for the selectivity process involved in the migration decision (based on observed and unobserved characteristics). This study finds that the productivity differential is the leading factor explaining migration. However, migration not only depends on individual characteristics, but strongly relies on the level of household education. Unfortunately, the initial disadvantages related to the household background determine that the one who faces attractive potential wage differentials is at the same time constrained by its household. The conclusion is that household-related migration costs are a source of inefficiency in labour allocation. Consequently, supporting the infrastructure in the rural economy is not the only way to achieve convergence across the territory. Subsidies aimed to reduce migration costs can be also considered in a framework oriented towards encouraging functional migration flows.
Keywords: R23; J31; J61; 330; migration; labour earnings; self-selection; labour markets; Binnenwanderung; Regionale Lohnstruktur; Regionale Disparität; Produktivität; Schätzung; Chile